The psychology of fear of crime. Conceptual and methodological perspectives - Greve, Werner (The British journal of criminology, 2003)
Since the very beginnings of research on the fear of crime in the early 1970s, authors have emphasized the need for theoretical clarification of the meaning and measurement of the concept. The present article outlines a theory of fear of crime from the psychological perspective. In particular, psychological concepts of emotions, most notably the state/trait distinction and the notion of emotions as involving multiple components, are applied to fear of crime. The outcome of this conceptual clarification is a two-dimensional taxonomy which can be used to differentiate between instruments applied to assess fear of crime. Finally, taking into account the results of psychological research on survey methodology, the practical value of this taxonomy for the assessment of fear of crime is discussed